Eksplorasi Faktor Perkembangan Tingkah Laku dan Bahasa Anak Usia Dini pada Masa Pandemi - Sariwati Muhamad; Lukman Tamhir (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to explore the factors that influence the development of behavior and language in early childhood during the pandemic. The type of this research is qualitative research. The subjects of this study were early childhood (2-3 years) totaling 4 children, as well as 4 mothers of these children. The data in this qualitative research were obtained through observation and interviews. Where observations were made on the activities of these children, while interviews were conducted on the mothers of these children. The results of this study indicate that there are factors that influence the development of behavior and language in early childhood during the pandemic. And the developmental factors of the four children are different. In general, the factors that influence the development of early childhood behavior consist of habits, imitation, family environment, media, and learning. While the factors that influence the language development of children consist of intelligence (the process of acquiring knowledge), parental experience/experience, educational status, number of children/number of family members, gender, and bilingualism.